(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the theoretical and methodological foundations of developing the professional competence of future social workers, the technological foundations of developing the professional competence of future social workers based on advanced foreign experiences are studied. The need to develop the professional competence of future social workers was also analyzed.